The dismantling of Japan's empire in East Asia: deimperialization, postwar legitimation and imperial afterlife - Kushner, Barak; Muminov, Sherzod (Routledge studies in the modern history of Asia, 2017)
"The end of Japan's empire appeared to happen very suddenly, and cleanly--but, as this book shows, it was in fact very messy, with a long period of establishing or re-establishing the postwar order. Moreover, as the authors argue, empires have afterlives, which, in the case of Japan's empire, is not much studied. This book considers the details of de-imperialization, including repatriation of Japanese personnel, the redrawing of boundaries, issues to do with prisoners of war and war criminals, new arrangements for democratic political institutions, for media and for the regulation of trade. It also discusses the continuing impact of empire: on the countries ruled or occupied by Japan, where as a result of Japanese management and administration, both formal and informal, patterns of behavior and attitudes were established which continued subsequently. This was true in Japan itself, where returning imperial personnel had to be absorbed and adjustments made to imperial thinking; and on present day East Asia, where the shadow of Japan's empire still lingers. This legacy of unresolved issues concerning the correct relationship of Japan, an important, energetic, outgoing nation and a potential regional 'hub,' with the rest of the region not comfortably settled in this era, remains a fulcrum of regional dispute"--Provided by publisher
Keywords: East Asia -- Relations -- Japan; Japan -- Foreign relations -- 1945-1989; Japan -- Relations -- East Asia; East Asia -- Politics and government -- 1945-; Aufsatzsammlung; Geschichte 1945-2015; Außenbeziehungen; Außenpolitik; Postkolonialismus; Korea; China; Japan